Effect of the tiger stripes on the deformation of Saturn's moon Enceladus. Issue 14 (24th July 2016) - Souček, Ondřej; Hron, Jaroslav; Běhounková, Marie; Čadek, Ondřej
Abstract: Enceladus is a small icy moon of Saturn with active jets of water emanating from fractures around the south pole, informally called tiger stripes, which might be connected to a subsurface water ocean. The effect of these features on periodic tidal deformation of the moon has so far been neglected because of the difficulties associated with implementation of faults in continuum mechanics models. Here we estimate the maximum possible impact of the tiger stripes on tidal deformation and heat production within Enceladus's ice shell by representing them as narrow zones with negligible frictional and bulk resistance passing vertically through the whole ice shell. Assuming a uniform ice shell thickness of 25 km, consistent with the recent estimate of libration, we demonstrate that the faults can dramatically change the distribution of stress and strain in Enceladus's south polar region, leading to a significant increase of the heat production in this area. Key Points: The presence of faults can significantly change the distribution of stress and strain in Enceladus's south polar region (SPR) The deformation induced by faults leads to local increases of heat flux by a factor of 10 and a twofold increase in SPR on average The effect of the faults on stress and strain is limited to SPR and is negligible at distances larger than 40 degrees from the south pole